Climate change, climatic variation and extreme biological responses. (19th June 2017) - Palmer, Georgina; Platts, Philip J.; Brereton, Tom; Chapman, Jason W.; Dytham, Calvin; Fox, Richard; Pearce-Higgins, James W.; Roy, David B.; Hill, Jane K.; Thomas, Chris D.
Abstract : Extreme climatic events could be major drivers of biodiversity change, but it is unclear whether extreme biological changes are (i) individualistic (species- or group-specific), (ii) commonly associated with unusual climatic events and/or (iii) important determinants of long-term population trends. Using population time series for 238 widespread species (207 Lepidoptera and 31 birds) in England since 1968, we found that population 'crashes' (outliers in terms of species' year-to-year population changes) were 46% more frequent than population 'explosions'. (i) Every year, at least three species experienced extreme changes in population size, and in 41 of the 44 years considered, some species experienced population crashes while others simultaneously experienced population explosions. This suggests that, even within the same broad taxonomic groups, species are exhibiting individualistic dynamics, most probably driven by their responses to different, short-term events associated with climatic variability. (ii) Six out of 44 years showed a significant excess of species experiencing extreme population changes (5 years for Lepidoptera, 1 for birds). These 'consensus years' were associated with climatically extreme years, consistent with a link between extreme population responses and climatic variability, although not all climatically extreme years generated excess numbers of extreme population responses. (iii) Links between extreme population changes and long-term population trends were absent in Lepidoptera and modest (but significant) in birds. We conclude that extreme biological responses are individualistic, in the sense that the extreme population changes of most species are taking place in different years, and that long-term trends of widespread species have not, to date, been dominated by these extreme changes. This article is part of the themed issue 'Behavioural, ecological and evolutionary responses to extreme climatic events'.